1988
DOI: 10.1159/000288095
|View full text |Cite
|
Sign up to set email alerts
|

Psychogenic Pain and Psychological Variables: a Psychometric Study

Abstract: A sample of 41 women suffering from psychogenic pain according to DSM-III diagnostic criteria were psychometrically studied, in order to ascertain if they showed specific psychological traits or mechanisms. Type A behavior, extraversion, neuroticism, psychoticism and dissimulation and hostility-aggressivity traits were the psychological variables studied both in the pain sample and in a matched control group. Psychogenic pain patients were significantly more neurotic and suspicious and less physically aggressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…In our study, we found a statistically significative correlation between neuroticism and catastrophizing, although this correlation was not clinically relevant ( p = 0.3783). Other descriptive studies in various chronic types of pain have found also high levels of neuroticism compared to control groups [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. Several studies have focused on the study of neuroticism as this trait may affect the adjustment to ongoing pain, increasing suffering and disability, and potentially contributing to the development of chronic pain [ 14 ].…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…In our study, we found a statistically significative correlation between neuroticism and catastrophizing, although this correlation was not clinically relevant ( p = 0.3783). Other descriptive studies in various chronic types of pain have found also high levels of neuroticism compared to control groups [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. Several studies have focused on the study of neuroticism as this trait may affect the adjustment to ongoing pain, increasing suffering and disability, and potentially contributing to the development of chronic pain [ 14 ].…”
Section: Discussionmentioning
confidence: 95%
“…The personality trait that has been most studied in chronic pain is neuroticism. A considerable number of studies have found higher levels of neuroticism compared to control groups in various chronic pain types [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. Other studies suggest that neuroticism may be a causal factor for chronic pain [ 14 , 26 , 27 , 28 ] and much research has focused on neuroticism as a moderator of the pain experience [ 29 ], through the creation of a heightened physical sensitivity to pain due to its inherent connection with chronically moderated anxiety [ 14 , 22 , 30 , 31 , 32 , 33 , 34 ] or influencing adjustment to pain by affecting pain-related beliefs and emotional distress [ 14 , 19 , 35 , 36 , 37 , 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation